Effect of Lipase Ionic Liquid Coating and Imprinting on Transesterification and Thermostability - M. Matsumoto; Y. Tahara (Chemical and Biochemical Engineering Quarterly)
This study investigates the effects of the treatments (substrate analogue imprinting and ionic liquid coating) on the catalytic activity and thermostability of lipase from Burkholderia cepacia in the transesterification of vinyl acetate with benzyl alcohol. The catalytic activity was significantly enhanced when the lipase was coated with a Brij 56-based ionic liquid or surfactant Brij 56. Notably, the ionic liquid coating had a greater effect than the imprinting treatment. The activity of the ionic liquid-coated lipase was over 50 times greater than that of the free lipase. Additionally, after incubation at 90 °C for 2 hours, the residual activity of the ionic liquid-coated lipase was about twice those of the other lipases. These findings demonstrate that the ionic liquid coating substantially improved both the reactivity and thermostability of the lipase compared to the native lipase.